The Impact of Educational Quality on Word-of-Mouth about Universitas Pancasila: The Mediating Role of Institutional Image among Senior High School Students in Depok City, West Java - Wahyudi, Ade; Setiarini, Setiarini; Irawan, Indra Ade; Refaldi Bremana Sitepu; Sarah Aini Salsabila (Sean Institute, 2025)
This study examines the impact of educational quality on word-of-mouth (WOM) about Universitas Pancasila, with institutional image serving as a mediating variable among senior high school students in Depok City, West Java. Using a quantitative explanatory approach and data collected from 150 respondents, the study employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) for analysis. The results reveal that educational quality significantly influences institutional image and WOM, while institutional image also exerts a significant positive effect on WOM. Furthermore, institutional image mediates the relationship between educational quality and WOM, indicating that a strong image enhances the effect of perceived educational quality on students’ willingness to share positive recommendations. These findings highlight the importance of maintaining high educational standards and a credible institutional image as key strategies to foster voluntary advocacy and strengthen university competitiveness within Indonesia’s higher education landscape.